Efficacy and Safety of Drug Elution Bead-Transarterial Chemoembolization in Advanced Soft Tissue Sarcoma - Albert, Albert; Manginstar, Christian O.; Saleh, Denny; Merung, Marselus A. (Medical Scope Journal, 2025)
Abstract: Soft-tissue sarcomas (STS) are rare and heterogeneous tumors originating from mesenchymal tissues. While surgical resection remains the primary treatment, not all patients are eligible for surgery, particularly in advanced stages. Drug-eluting bead transarterial chemoemboli zation (DEB-TACE) is a promising therapeutic option for such cases. This retrospective study evaluated the efficacy and safety of DEB-TACE in 30 patients with advanced STS at Prof. Dr. R. D. Kandou Hospital, Manado, from 2020 to 2023. The overall response rate (ORR) was 76.7% (p<0.05), with five patients achieving complete response and 18 showing partial response. The main adverse reactions included post-embolization syndrome (fever, pain, nausea, vomiting) and grade II or higher bone marrow suppression. Despite a morbidity rate of 93.3%, no treatment-related mortality was observed. In conclusion, DEB-TACE is an effective and safe treatment for advanced STS, providing superior short-term efficacy compared to traditional systemic chemotherapy. Keywords: soft tissue sarcoma; drug eluting bead; transarterial chemoembolization